Association between global DNA methylation (LINE-1) and occupational particulate matter exposure among informal electronic-waste recyclers in Ghana. Issue 11 (2nd November 2022) - Issah, Ibrahim; Arko-Mensah, John; Rozek, Laura S.; Rentschler, Katie; Agyekum, Thomas P.; Dwumoh, Duah; Batterman, Stuart; Robins, Thomas G.; Fobil, Julius N.
ABSTRACT: This study examined the associations between PM (2.5 and 10) and global DNA methylation among 100 e-waste workers and 51 non-e-waste workers serving as controls. Long interspersed nucleotide repetitive elements-1 (LINE-1) was measured by pyrosequencing. Personal PM2.5 and PM10 were measured over a 4-hour work-shift using real-time particulate monitors incorporated into a backpack . Linear regression models were used to assess the association between PM and LINE-1 DNA methylation. The concentrations of PM2.5 and PM10 were significantly higher among the e-waste workers than the controls (77.32 vs 34.88, p < 0.001 and 210.21 vs 121.92, p < 0.001, respectively). PM2.5 exposure was associated with increased LINE-1 CpG2 DNA methylation (β = 0.003; 95% CI; 0.001, 0.006; p = 0.022) but not with the average of all 4 CpG sites of LINE-1. In summary, high levels of PM2.5 exposure was associated with increased levels of global DNA methylation in a site-specific manner.